0936 The curious case of the shepherd and the dogs severe acute meningovasculitis: return of the great imitator. (1st December 2017) - Jaffer, Fatima; Ashraghi, Mohammad; Nadarajah, Ramesh; Sibtain, Naomi; Britton, Tom
Abstract : A 40-year-old male presented as a wake-up stroke with right hemiparesis and aphasia consistent with a left MCA territory infarct. Rapid deterioration within 24 hours resulted in intubation thought to be secondary to malignant MCA syndrome. Within 48 hours, he had acquired new, multi-territory infarcts leading to tetraparesis. Initial 'routine' young stroke work-up was unyielding. MRI/MRA suggested vasculitis and CSF analysis revealed raised protein, lymphocytosis, and low glucose ratio with negative gram stain, culture and virology. HIV test was negative. Broad-spectrum antibiotics were commenced with anti-TB cover, pending results. Steroids were administered given diagnostic uncertainty whilst empirical treatment with cyclophosphamide was considered. Interval MRI at one-week post treatment showed significant improvement in vasculitis prompting testing for syphilis. Revisiting the history, the patient was in a same sex relationship and had a prodrome of increasing headaches, anorexia, insomnia, personality change and a palmar rash diagnosed as contact dermatitis, eight weeks prior to admission. Neurosyphilis was confirmed: serum RPR 1:32, TPPA>1:1280, positive EIA; CSF RPR 1:8 and TPPA>1:1280. He was treated with an extended course of antibiotics with slow improvement. We review the challenges in reaching a diagnosis and the latest BASHH guidelines – in this increasingly prevalent disease.